Overview of surface measurements and spatial characterization of submicrometer particulate matter during the DISCOVER-AQ 2013 campaign in Houston, TX. (3rd August 2017) - Leong, Y.J.; Sanchez, N.P.; Wallace, H.W.; Karakurt Cevik, B.; Hernandez, C.S.; Han, Y.; Flynn, J.H.; Massoli, P.; Floerchinger, C.; Fortner, E.C.; Herndon, S.; Bean, J.K.; et al.
ABSTRACT: The sources of submicrometer particulate matter (PM1 ) remain poorly characterized in the industrialized city of Houston, TX. A mobile sampling approach was used to characterize PM1 composition and concentration across Houston based on high-time-resolution measurements of nonrefractory PM1 and trace gases during the DISCOVER-AQ Texas 2013 campaign. Two pollution zones with marked differences in PM1 levels, character, and dynamics were established based on cluster analysis of organic aerosol mass loadings sampled at 16 sites. The highest PM1 mass concentrations (average 11.6 ± 5.7 µg/m 3 ) were observed to the northwest of Houston (zone 1), dominated by secondary organic aerosol (SOA) mass likely driven by nighttime biogenic organonitrate formation. Zone 2, an industrial/urban area south/east of Houston, exhibited lower concentrations of PM1 (average 4.4 ± 3.3 µg/m 3 ), significant organic aerosol (OA) aging, and evidence of primary sulfate emissions. Diurnal patterns and backward-trajectory analyses enable the classification of airmass clusters characterized by distinct PM sources: biogenic SOA, photochemical aged SOA, and primary sulfate emissions from the Houston Ship Channel. Principal component analysis (PCA) indicates that secondary biogenic organonitrates primarily related with monoterpenes are predominant in zone 1 (accounting for 34% of the variability in the data set). The relevance of photochemical processes and industrial and traffic emission sources in zone 2 also is highlighted by PCA, which identifies three factors related with these processes/sources (~50% of the aerosol/trace gas concentration variability). PCA reveals a relatively minor contribution of isoprene to SOA formation in zone 1 and the absence of isoprene-derived aerosol in zone 2. The relevance of industrial amine emissions and the likely contribution of chloride-displaced sea salt aerosol to the observed variability in pollution levels in zone 2 also are captured by PCA. Implications : This article describes an urban-scale mobile study to characterize spatial variations in submicrometer particulate matter (PM1 ) in greater Houston. The data set indicates substantial spatial variations in PM1 sources/chemistry and elucidates the importance of photochemistry and nighttime oxidant chemistry in producing secondary PM1 . These results emphasize the potential benefits of effective control strategies throughout the region, not only to reduce primary emissions of PM1 from automobiles and industry but also to reduce the emissions of important secondary PM1 precursors, including sulfur oxides, nitrogen oxides, ammonia, and volatile organic compounds. Such efforts also could aid in efforts to reduce mixing ratios of ozone.